Intervensi Psikologis Pada Peneriksaan KDRT (Kekerasan Dalam Rumah Tangga) Dalam PPA (Perlindungan Perempuan dan Anak) Di POLRESTA Malang - Judiari, Josina (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2013)
Psychological intervention aimed at analyzing the motif of the informer or victim of the domestic violence and if it is needed, the reported party can be examined his psychological condition. Some test items that selected for the condition are MMPI Test (Mineesole Multiplanic Personality Inventory) that able to display 18 psychological aspects and the mostly highlighted in the initial investigation is the informer honesty. If the score do not fulfill the requirements it is important notes for the investigators to be careful and not accept without ceremony the victim complaints. Color test is personality test that able to reveal the situation target, behavior under pressure or the actual problems. The last, the violence victim can be occurred in the domestic area because the victim give opportunities for the violence occurrence for example too dominant, too sensitive or too relax, do not think her spouse if look at from NSQ (Neurotic Scale Questionaire).